Effects of state immigrant insurance coverage policies on access to adequate prenatal care among immigrant pregnant women in the United States - Gunah Kim; S. Wilton Choi; Younhee Kim (Journal of Migration and Health)
Background: The 1996 federal welfare and immigration reform restricted immigrant eligibility for public health insurance such as Medicaid and CHIP. As of January 2023, 34 states have adopted policies to expand insurance coverage for immigrant pregnant individuals through Medicaid/CHIP. Objective: To estimate the effects of state immigrant insurance policies on prenatal care utilization and timing among pregnant immigrants. Methods: A difference-in-differences approach was used to compare states that expanded immigrant insurance coverage to those that did not. The main data source is the restricted natality data from the National Center for Health Statistics, including all singleton births to immigrant mothers aged 15–44 across all 50 states and D.C. from 2015 to 2019. Results: In states adopting the State-only funds option, publicly insured immigrants had higher odds of receiving intermediate (OR: 1.429; 95 % CI: 1.210–1.687), adequate (OR: 1.723; 95 % CI: 1.526–1.946), and adequate plus (OR: 1.373; 95 % CI: 1.256–1.500) prenatal care, and lower odds of inadequate care (OR: 0.480; 95 % CI: 0.406–0.568) compared to uninsured immigrants. Additionally, this policy was associated with an 87.1 percentage point increase in first-trimester care initiation (95 % CI: 1.622–2.159), and significant decreases in delayed care (−43.8 pp; 95 % CI: 0.430–0.736) and no care until delivery (−67.3 pp; 95 % CI: 0.204–0.522) for publicly insured immigrant populations compared to uninsured immigrants. Conclusions: Expanding immigrant insurance coverage was associated with earlier and more adequate prenatal care. However, only State-only funds showed consistent improvements in the adequacy of prenatal care utilization.